Aplicando criptografia no formato de rotação por estações de aprendizagem - Lima, Eduardo Rodrigues (Universidade Federal de São Carlos, 2024)
This paper explores the use of cryptography in the classroom with 8th and 9th grade classes in a regular school in the interior of the state of São Paulo. The content was covered in 6 class hours (300 minutes), starting with theoretical concepts already studied, such as prime numbers and divisibility, and moving on to the practical application of the activity of rotating through learning stations. In these activities, students faced deciphering and coding challenges, educational games, and individual and group tests. Although the RSA method requires knowledge of congruence and modular arithmetic, the coding and decoding steps were adapted to facilitate student understanding. The process involved moments of discussion, collaborative practice, competition, and fun, contributing to the development of new skills and the review of Mathematical concepts already worked on. The objective was to investigate the integration of Mathematical theory with practical activities, allowing students to see Mathematics beyond the abstract. With this approach, topics often seen only in theory gain a new perspective and become closer to the students' reality.
Applying encryption in a rotation model for learning stations
Keywords: Criptografia RSA; Aritmética Modular; Ensino de Matemática; Rotação por Estações; RSA Cryptography; Modular Arithmetic; Mathematics Teaching; Station Rotation; CIENCIAS EXATAS E DA TERRA::MATEMATICA